Neuronal toll-like receptor 4 signaling induces brain endothelial activation and neutrophil transmigration in vitro. - BOWIE, ANDREW (My University, 2012)
Background: The innate immune response in the brain is initiated by pathogen-associated molecular patterns (PAMPS) or danger-associated molecular patterns (DAMPS) produced in response to central nervous system (CNS) infection or injury. These molecules activate members of the Toll-like receptor (TLR) family, of which TLR4 is the receptor for bacterial lipopolysaccharide (LPS). Although neurons have been reported to express TLR4, the function of TLR4 activation in neurons remains unknown. Methods: TLR4 mRNA expression in primary mouse glial and neuronal cultures was assessed by RT-PCR. Mouse mixed glial, neuronal or endothelial cell cultures were treated with LPS in the absence or the presence of a TLR4 specific antagonist (VIPER) or a specific JNK inhibitor (SP600125). Expression of inflammatory mediators was assayed by cytometric bead array (CBA) and ELISA. Activation of extracellular-signal regulated kinase 1/2 (ERK1/2), p38, c-Jun-N-terminal kinase (JNK) and c-Jun was assessed by Western blot. The effect of conditioned media of untreated- versus LPS-treated glial or neuronal cultures on endothelial activation was assessed by neutrophil transmigration assay, and immunocytochemistry and ELISA were used to measure expression of intercellular cell adhesion molecule (ICAM-1) and vascular cell adhesion molecule (VCAM-1). Results: LPS induces strong release of the chemokines RANTES and CXCL1 (KC), tumor necrosis factor- ? (TNF ? ) and IL-6 in primary mouse neuronal cultures. In contrast, LPS induced release of IL-1 ? , IL-1 ? and granulocyte-colony stimulating factor (G-CSF) in mixed glial, but not in neuronal cultures. LPS-induced neuronal KC expression and release were completely blocked by VIPER. In glial cultures, LPS induced activation of ERK1/2, p38 and JNK. In contrast, in neuronal cultures, LPS activated JNK but not ERK1/2 or p38, and the specific JNK inhibitor SP600125 significantly blocked LPS-induced KC expression and release. Finally, conditioned medium of LPS-treated neuronal cultures induced strong expression of ICAM-1 and VCAM-1 on endothelial cells, and induced infiltration of neutrophils across the endothelial monolayer, which was inhibited by VIPER. Conclusion: These data demonstrate for the first time that neurons can play a role as key sensors of infection to initiate CNS inflammation.
PUBLISHED
Keywords: Neurons, Toll-like receptors, Lipopolysaccharide, Neutrophils, Chemokines, Endothelial cells; Neurons, Toll-like receptors, Lipopolysaccharide, Neutrophils, Chemokines, Endothelial cells